The 3p Concept to Employee Job Satisfaction and The Impact on Organizational Performance (International Journal of Psychosocial Rehabilitation, 2020)
Banks are a business entity that is managed by human resources in achieving goals. Overall performance improvement is important for the bank to encounter business competition. At the BJB Tasikmalaya, employee performance is at an optimal condition. It may be seen from the condition of employees who dealt with oversight while working; resulting the job performance quality is not in line with BJB standards. This study discussed the effect of compensation with the 3P concept on employee job satisfaction and its effect on organizational performance at the BJB Tasikmalaya. The sample was selected by 100 employees from 13 branches. Multiple regression analysis was performed by test the validity and reliability and test the classical assumptions. The results showed that there was an influence between the 3P concept on employee job satisfaction at BJB Tasikmalaya and job satisfaction on organizational performance.